Ex-ante Evaluation of European ICTs Policies: Efficiency vs Cohesion Scenarios - Roberta Capello; Alessia Spairani (European Regional Science Association (ERSA), 2004)
Normative interventions in the ICTs sector at the European level are in fact mainly driven by the idea that the impacts of advanced telecommunications technology adoptions are related both to their capacity to increase competitiveness and to their potential influence on regional disparities, enhancing growth rates and development of weaker and less developed regions. The result is that the well-known trade-off between efficiency and cohesion emerges quite evidently. In this paper, the aim is to provide an ex-ante evaluation of EU ICTs policies on regional development and regional disparities, through a scenario building methodology which allows to calculate the increase in per capita GDP at NUTS 2 level for all 15 EU member states according to efficiency or cohesion policy options. In particular, the aims are to provide a cost assessment of efficiency and cohesion ICTs policies and to detect different regional response to ICTs policies, by highlighting different behavioural attitudes and reacting capacities of regions in front of alternative ICTs policy scenarios.
Keywords: 330